Laparoscopic management of liver echinococcal cyst at B.P.Koirala Institute of Health Sciences Dharan, Nepal an institutional review - Sah, Suresh Prasad; Adhikary, S; Agrawal, CS; Gupta, R; Ghimire, A (Health Renaissance, 2017)
Background: Hydatid disease is an endemic disease in several parts of the world. Surgeons and physicians in the non-endemic areas may encounter the disease. Surgery remains the mainstay of therapy. Recently, laparoscopic treatment of hepatic hydatid disease has been increasingly popular and has undergone a revolutionary parallel to the progress in laparoscopic surgery. It is a new and encouraging approach with minimum morbidity and mortality. Objective: To assess the outcome of laparoscopic management of hydatid cyst. Methods: A retrospective & prospective case series study included all patients of hydatid liver cysts who were managed laparoscopically from 1st January 2008- 31st June 2013 (five & half yrs). Patients with deep intraparenchymal location of the cyst, more than 3 cysts and cysts with calcified walls were excluded. Results: Thirty two patients were included in this study to know the results of the laparoscopic management of hepatic hydatid cyst disease. Majority of patients in the age group of 21-40 years. The mean age was of 38± 5.25 with range being 19-65 years. The commonest presentation of dull aching pain in right upper quadrant was seen in 21(62.5%) patients followed by hepatomegaly in 12 (37.5%) patients & right upper abdominal lump in 8 (25%) patients. Twenty seven (84.3%) patients had single cyst & 5 (15.6%) patients had two cysts. The mean diameter of the cyst was 9.2±2.72 cm in size. The mean operative time was (65.42±12.67min) with range being 45-125 mins. Conclusion: The laparoscopic approach is safe & feasible in selected patients. The treatment choices of hydatid disease of the liver have increased in the last 2 decades including medical treatment, percutaneous drainage, or a combination. Health Renaissance 2015;13 (1): 86-94